Urban park and physical activities among residents in Klang Valley / Nurul Haqimah Mohd Noor Azudin and Norfashiha Hashim - Mohd Noor Azudin, Nurul Haqimah; Hashim, Norfashiha (2018)
Urban park is a green space that is located in the center of cities which corporate places to offer recreation and green areas to publics. The purpose of research is to investigate the relationship of urban park and physical activities among residents in Klang Valley. This research attempts to study the elements of urban parks in Malaysia, determine the users’ acceptance towards urban park and to highlight the relationship between users’s satisfactions and use pattern of urban parks. Questionnaires were used to collect the data and they were analyzed by Statistical Packaging for Social Science. Data was collected in these three parks which are Taman Tasik Perdana, Taman Tasik Shah Alam and Taman Bukit Kiara. 19.7% of findings shows that the urban parks were not maintained well in order to serve the publics. For example, tree and turf in the parks were not properly chosen to give comfort to the public. Most of the parks have their own elements to serve the public such as shaded area, open areas, pathway design, facilities, activity zones and others. Findings also indicate that most users were generally satisfied with the facilities provided in the park. By using correlation analysis, it indicates that the satisfaction level of the urban park elements will influence the users’ use pattern in the park. This research has been successfully analyzed which elements of parks will determine the users’ satisfaction and use pattern in parks. This research can provide useful information for interpreting user patterns, and in particular, when designing and assessing interventions intended to improve the amount and intensity of physical activity.